Amino acid starvation‐induced LDLR trafficking accelerates lipoprotein endocytosis and LDL clearance. (7th January 2022) - Chen, Ye; Wu, Xiao; Zhang, Jing; Pan, Guopin; Wang, Xiaoyun; Guo, Xiaosun; Wang, Jianli; Cui, Xiaopei; Gao, Haiqing; Cheng, Mei; Yang, Jingwen; Zhang, Cheng; et al.
Abstract: Mammalian cells utilize Akt‐dependent signaling to deploy intracellular Glut4 toward cell surface to facilitate glucose uptake. Low‐density lipoprotein receptor (LDLR) is the cargo receptor mediating endocytosis of apolipoprotein B‐containing lipoproteins. However, signaling‐controlled regulation of intracellular LDLR trafficking remains elusive. Here, we describe a unique amino acid stress response, which directs the deployment of intracellular LDLRs, causing enhanced LDL endocytosis, likely via Ca 2+ and calcium/calmodulin‐dependent protein kinase II‐mediated signalings. This response is independent of induction of autophagy. Amino acid stress‐induced increase in LDL uptake in vitro is comparable to that by pravastatin. In vivo, acute AAS challenge for up to 72 h enhanced the rate of hepatic LDL uptake without changing the total expression level of LDLR. Reducing dietary amino acids by 50% for 2 to 4 weeks ameliorated high fat diet‐induced hypercholesterolemia in heterozygous LDLR ‐deficient mice, with reductions in both LDL and VLDL fractions. We suggest that identification of signaling‐controlled regulation of intracellular LDLR trafficking has advanced our understanding of the LDLR biology, and may benefit future development of additional therapeutic strategies for treating hypercholesterolemia. Synopsis: At the cellular level, amino acid starvation triggers translocation of intracellular LDLRs to the cell surface, causing enhanced LDL endocytosis. At the systemic level, dietary amino acid restriction enhances clearance of LDL cholesterol from the circulation. Removal of extracellular amino acids promotes LDLR trafficking to the cell surface, leading to enhanced LDL endocytosis This response is mediated by Ca 2+ ‐ and CaMKII‐dependent signaling which redistributes intracellular LDLRs to the fast recycling route In heterozygous LDLR +/− mice, dietary amino acid restriction ameliorates high fat‐induced hypercholesterolemia Abstract : At the cellular level, amino acid starvation triggers translocation of intracellular LDLRs to the cell surface, causing enhanced LDL endocytosis. At the systemic level, dietary amino acid restriction enhances clearance of LDL cholesterol from the circulation.